A preparation method of far infrared negative ion inorganic coating

The far-infrared negative ion inorganic coating prepared through fine chemical steps solves the problems of unstable performance and poor functional durability in the existing inorganic coating preparation process, and achieves efficient far-infrared emission and negative ion release, which is suitable for environmental protection and healthy living needs.

CN119752227APending Publication Date: 2025-04-04林以进
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411886543.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The current inorganic coating preparation process with far-infrared emission and negative ion release functions on the market has problems such as low production efficiency, unstable product performance and poor functional durability, which is difficult to meet the needs of environmental protection and healthy living.

Method used

By accurately weighing inorganic binders, far-infrared emitting materials, negative ion generation materials, fillers and auxiliary agents, grinding, drying, mixing, dispersing and grinding, far-infrared negative ion inorganic coatings are prepared. The method includes multiple grinding and dispersion steps to ensure material particle size refinement and uniform dispersion of components.

Benefits of technology

The prepared far-infrared negative ion inorganic coating has high physical and chemical stability, can effectively emit far-infrared rays and release negative ions, promote blood circulation, purify air, and have excellent adhesion, weather resistance and corrosion resistance, and is suitable for a variety of places.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752227A_ABST
    Figure CN119752227A_ABST
Patent Text Reader

Abstract

The invention discloses a highly efficient production and preparation method of a far-infrared negative ion inorganic coating, and relates to the technical field of negative ion coating preparation. First, the raw materials are accurately prepared, and the inorganic binder is selected from a variety of silica sols, etc., and is matched with specific far-infrared emission, negative ion generating materials and fillers, and additives. The key materials are pre-treated and mixed, and dispersed at a high speed of 1000-3000r / min for 30-60min, ground with a sand mill to a slurry fineness of less than 50μm, and then the color and viscosity are adjusted. Each raw material is finely proportioned by weight, such as the proportion of each component of the inorganic binder is set as needed, and the parameters of the grinding and dispersing equipment are strictly controlled, such as the ball-to-material ratio, the cooling temperature, etc. The finished product is tested, and the far-infrared emissivity is not less than 0.85, and the negative ion release per cubic centimeter is not less than 1000. This method is efficient and simple, the coating is environmentally friendly and durable, and has good decorative properties, and has broad prospects in the fields of home decoration and construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating production and preparation, and in particular relates to a preparation method of far-infrared negative ion inorganic coating. Background Art

[0002] As the modern construction and home decoration industries are booming, coatings, as key materials, have attracted much attention for their performance and environmental attributes. Traditional organic coatings have high emissions of volatile organic compounds (VOCs), which not only harm indoor air quality and affect the health of residents, but also pollute the atmospheric environment, and are gradually unable to meet increasingly stringent environmental standards.

[0003] In recent years, many health problems have occurred due to the use of inferior organic paints for interior decoration. For example, in a newly built residential area, many owners began to experience symptoms such as dizziness, fatigue, and respiratory discomfort soon after moving in. Professional testing found that harmful substances such as formaldehyde and benzene in the indoor air seriously exceeded the standard. After tracing the source, it was determined that the culprit was the traditional organic paint applied on the wall. The harmful gases that continued to volatilize accumulated in the closed space, causing great trouble to the lives of residents, and even caused some children to have a weakened immunity and frequent illnesses and medical treatment.

[0004] At the same time, consumers are pursuing higher quality in their living and working environments, and they expect that coatings can give spaces additional health functions in addition to basic decorative functions. Far infrared rays have a positive effect on human blood circulation and metabolism, while negative ions can effectively purify the air and soothe nerves. Integrating these two functions into an inorganic coating system can not only comply with the general trend of environmental protection, but also fit the trend of healthy living. However, the preparation process of such inorganic coatings with both far infrared emission and negative ion release functions in the current market is still immature, and there are problems such as low production efficiency, unstable product performance, and poor functional durability, which need to be overcome urgently. Summary of the invention

[0005] The object of the present invention is to provide a far-infrared negative ion inorganic coating in order to solve the above-mentioned problems.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] The invention discloses a preparation method of a far-infrared negative ion inorganic coating, which specifically comprises the following steps:

[0008] S1. Accurately weigh an inorganic binder, a far-infrared emitting material, a negative ion generating material, a filler and an auxiliary agent as raw materials for preparation, wherein the inorganic binder is selected from one or more combinations of silica sol, water glass and phosphate; the far-infrared emitting material is selected from one or more combinations of tourmaline, Bian stone, medical stone and far-infrared ceramic powder; the negative ion generating material is selected from one or more combinations of tourmaline powder, negative ion powder and opal; the filler is selected from one or more combinations of calcium carbonate, talc, titanium dioxide and wollastonite; the auxiliary agent includes a dispersant, a defoamer, a leveling agent and a thickener;

[0009] S2, subjecting the far-infrared emitting material and the negative ion generating material to a grinding process in sequence to refine the material particle size to a predetermined range, and then performing a drying process to remove moisture therein, thereby achieving the effect of preventing the material from agglomerating in subsequent processes;

[0010] S3. Put the pre-treated far infrared emitting material and negative ion generating material, as well as a predetermined amount of inorganic binder, filler and additive into a professional mixing equipment, and use mechanical stirring or high-speed dispersion means to promote uniform mixing of the components to form a mixed material;

[0011] S4, placing the mixed material into a high-speed dispersing device, setting the dispersing speed to be in the range of 1000-3000 r / min, and continuing the dispersing time for 30-60 min to ensure that each component in the material reaches a more refined and stable dispersion state;

[0012] S5. Use a sand mill to grind the high-speed dispersed material until the material is ground into slurry, and the fineness of the slurry is precisely controlled to less than 50μm to ensure the fineness of the coating particles.

[0013] S6. Add appropriate pigments to the slurry obtained by grinding, accurately mix the target color, and at the same time, add appropriate amount of thickener to carefully adjust the slurry viscosity according to the construction standards, and finally obtain the finished far-infrared negative ion inorganic coating.

[0014] The present invention has at least the following beneficial effects: the far-infrared negative ion inorganic coating prepared by the present invention is mainly based on inorganic raw materials, eliminates VOC emissions, meets environmental protection standards, is suitable for various places, and protects ecological and human health. The far-infrared negative ion inorganic coating has high physical and chemical stability, and contains specific materials that can promote blood circulation and metabolism, purify the air and regulate nerves, and improve environmental quality; at the same time, it has excellent performance, good adhesion, weather resistance and corrosion resistance, and good decorative effect; it has wide adaptability and can be flexibly adjusted as needed to meet diverse needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The invention discloses a preparation flow chart of a method for preparing a far-infrared negative ion inorganic coating. DETAILED DESCRIPTION

[0016] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0017] like Figure 1 Shown

[0018] Example 1

[0019] A method for preparing a far-infrared negative ion inorganic coating comprises the following steps:

[0020] Select 30 parts of silica sol and 15 parts of water glass, mix the two to provide good bonding properties for the paint and ensure that the paint is firmly attached to the wall. Use 12 parts of tourmaline and 8 parts of far-infrared ceramic powder. The two materials work synergistically to effectively emit far-infrared rays and create a beneficial and healthy environment indoors. Prepare 15 parts of tourmaline powder and 10 parts of negative ion powder to ensure that the paint can stably release negative ions after use and purify the indoor air. Weigh 20 parts of calcium carbonate and 10 parts of talcum powder, which will help increase the volume of the paint, reduce costs, and improve the paint's application performance and hiding power. Add 2 parts of dispersant, 1 part of defoamer, 1.5 parts of leveling agent and 3 parts of thickener to evenly disperse the components of the paint, avoid bubbles, ensure a smooth coating, and adjust to the appropriate construction viscosity.

[0021] Tourmaline, far-infrared ceramic powder, tourmaline powder and negative ion powder are then put into a planetary ball mill, using zirconium oxide balls as the grinding medium, setting the ball-to-material ratio to 4:1, and controlling the grinding time to about 3 hours. The material particle size is refined to an average particle size of about 10 μm, and then dried in a vacuum drying oven at 60°C for 4 hours to remove moisture and prevent subsequent agglomeration.

[0022] Put the pretreated far-infrared emitting material, negative ion generating material together with the weighed inorganic binder, filler and additive into a high-speed disperser. First, stir at a low speed of 500r / min for 15 minutes to make the ingredients initially mixed evenly. Then switch to the high-speed dispersion mode of 2000r / min and continue stirring for 40 minutes to ensure that the ingredients are fully integrated to form a mixture with uniform texture.

[0023] The mixed material is transferred to a high-speed dispersing device with a cooling jacket, and the dispersing speed is set to 2500r / min and the dispersing time is set to 45 minutes. During the dispersing process, cooling water is circulated through the cooling jacket to keep the material temperature at around 30°C, ensuring that the components in the material are dispersed in a more refined and stable state.

[0024] A sand mill is used to grind the high-speed dispersed material. Silicon carbide beads are filled inside the sand mill as grinding media. The bead diameter is controlled at about 1 mm and the filling rate is 80%. The material is ground until it becomes a slurry, and the fineness of the slurry reaches less than 40μm, ensuring the fineness of the coating particles and making the final film-forming effect better.

[0025] According to the requirements of interior decoration style, add an appropriate amount of iron oxide pigment to the ground slurry for color adjustment, such as adding 0.5 parts of iron oxide red pigment to prepare a light red tone, and use hydroxyethyl cellulose thickener, slowly add and stir evenly, and check the viscosity while adding, and adjust the paint viscosity to 100KU (25℃, coat-4 cups) to obtain a far-infrared negative ion inorganic paint product that meets the requirements of indoor wall construction.

[0026] After testing, it was found that after the finished product was installed on the indoor wall, the far-infrared emissivity could reach 0.88, and the amount of negative ions released per cubic centimeter of space was stable at around 1,100, meeting the needs of ordinary residences for environmental protection and health functions.

[0027] Example 2

[0028] A method for preparing a far-infrared negative ion inorganic coating comprises the following steps:

[0029] 25 parts of phosphate are selected, which has good chemical stability and water resistance, and is suitable for long-term use in commercial places. 10 parts of Bian stone and 10 parts of medical stone are used, which can continuously emit far infrared rays to create a comfortable environment for public areas. 18 parts of opal and 12 parts of tourmaline powder are prepared to ensure that negative ions can be effectively released in public areas with frequent personnel flow to improve air quality. 15 parts of titanium dioxide and 10 parts of wollastonite are weighed to improve the hiding power and wear resistance of the paint to cope with more personnel contact and friction in public areas. 2.5 parts of dispersant, 1.2 parts of defoamer, 2 parts of leveling agent and 3.5 parts of thickener are added to optimize the construction performance of the paint and ensure uniform film formation when applied over a large area.

[0030] The Bian stone, medical stone, opal and tourmaline powder were pretreated using a planetary ball mill with zirconium oxide balls as the grinding medium. The ball-to-material ratio was set to 3.5:1 and the grinding time was about 3.5 hours. The material particle size was refined to an average particle size of about 8μm. Then, it was dried at 50°C for 5 hours using a low-temperature hot air dryer to completely remove moisture and prepare for subsequent processing.

[0031] The pretreated materials, phosphates, fillers and additives are put into professional mixing equipment together. They are first mechanically stirred at a speed of 600r / min for 20 minutes, and then switched to a high-speed dispersion mode of 2500r / min and stirred continuously for 50 minutes to ensure that all ingredients are evenly mixed to form a mixed material.

[0032] The mixed material is placed in a high-speed dispersing device, and the dispersing speed is set to 2800r / min and the dispersing time is set to 50 minutes. During the dispersing process, the material temperature is controlled at around 35°C through the cooling jacket, so that the various components in the material can be finely and stably dispersed, thereby improving the overall performance of the coating.

[0033] The material is ground using a sand mill filled with silicon carbide beads (bead diameter 1.2mm, filling rate 75%) as grinding media, and ground until the slurry fineness is less than 35μm, ensuring the fineness and texture of the paint, making its decorative effect in public areas more beautiful and lasting.

[0034] According to the overall decoration tone of commercial office spaces, titanium chrome pigments are added for color adjustment. For example, a proper amount of titanium chrome yellow pigment is added to mix a bright yellow tone. Then, a polyurethane associative thickener is used to adjust the viscosity. The viscosity is controlled at 110KU (25°C, coating -4 cups) to obtain a far-infrared negative ion inorganic paint product suitable for use in public areas of commercial offices.

[0035] After actual application testing, the paint can achieve a far-infrared emissivity of 0.92 after construction in public areas of commercial office spaces, release no less than 1,200 negative ions per cubic centimeter of space, and has good wear and pollution resistance, effectively meeting the use requirements of commercial spaces.

[0036] Example 3

[0037] A method for preparing a far-infrared negative ion inorganic coating comprises the following steps:

[0038] 40 parts of silica sol are used, and its good chemical corrosion resistance makes it suitable for wall protection in industrial environments that may be exposed to various chemical substances; 15 parts of far-infrared ceramic powder are selected to ensure that the far-infrared emission function can also be exerted in industrial plants, which helps to improve the working environment in the plant; 20 parts of negative ion powder are prepared to ensure the continuous release of negative ions in relatively closed industrial plants that may have certain air pollution, purify the air, and protect the health of workers.

[0039] Weigh 30 parts of calcium carbonate and 15 parts of talcum powder to improve the filling and hiding power of the paint, while reducing costs to meet the needs of large-area painting in industrial plants; add 3 parts of dispersant, 1.5 parts of defoaming agent, 2.5 parts of leveling agent and 4 parts of thickener to ensure that the paint can be evenly dispersed and smoothly constructed under the complex construction conditions of industrial plants.

[0040] The far-infrared ceramic powder and negative ion powder were pretreated using a planetary ball mill with zirconia balls as the grinding medium. The ball-to-material ratio was set to 4.5:1 and the grinding time was 4 hours. The material particle size was refined to an average particle size of about 12 μm, and then dried in a vacuum drying oven at 70°C for 3 hours to remove moisture and prevent agglomeration.

[0041] The pretreated material, silica sol, filler and additives were put into a high-speed disperser, first stirred at a low speed of 400 r / min for 20 minutes, then switched to a high-speed dispersion mode of 2200 r / min and continued stirring for 45 minutes to fully mix the ingredients to form a mixed material.

[0042] The mixed material was transferred to a high-speed dispersing device, and the dispersing speed was set to 2200 r / min and the dispersing time was set to 55 minutes. During the dispersing process, the material temperature was controlled at about 28°C by the cooling jacket to ensure that the various components in the material were finely and stably dispersed.

[0043] The material is ground using a sand mill, which is filled with silicon carbide beads (bead diameter 0.9 mm, filling rate 82%) as grinding media. The material is ground until the slurry fineness is less than 45 μm, which improves the fineness of the coating and makes the coating surface smoother and easier to clean and maintain.

[0044] According to the overall color planning of the industrial plant, inorganic pigments are added for color adjustment. For example, an appropriate amount of black iron oxide pigment is added to mix a gray tone, and then the viscosity is adjusted using hydroxyethyl cellulose thickener. The coating viscosity is adjusted to 90KU (25°C, coating -4 cups) to obtain a far-infrared negative ion inorganic coating product suitable for industrial plant wall protection and decoration.

[0045] After actual application tests in industrial plants, the paint's far-infrared emissivity can reach 0.85, the amount of negative ions released per cubic centimeter of space can be stabilized at around 1,000, and it has good tolerance to common industrial acids, alkalis and other chemical substances. The coating has strong adhesion and can effectively play a dual role of protection and decoration.

[0046] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a far-infrared negative ion inorganic coating, characterized in that: The following steps are involved: S1, weighing an inorganic binder, a far-infrared emitting material, a negative ion generating material, a filler and an auxiliary agent as raw materials for preparation, wherein the inorganic binder is selected from one or more combinations of silica sol, water glass and phosphate; the far-infrared emitting material is selected from one or more combinations of tourmaline, Bian stone, medical stone and far-infrared ceramic powder; the negative ion generating material is selected from one or more combinations of tourmaline powder, negative ion powder and opal; the filler is selected from one or more combinations of calcium carbonate, talc, titanium dioxide and wollastonite; the auxiliary agent includes a dispersant, a defoamer, a leveling agent and a thickener; S2, subjecting the far-infrared emitting material and the negative ion generating material to a grinding process in sequence to refine the material particle size to a predetermined range, and then performing a drying process to remove moisture therein, thereby achieving the effect of preventing the material from agglomerating in subsequent processes; S3, putting the far infrared emitting material and negative ion generating material after pretreatment, and a predetermined amount of inorganic binder, filler and additive into a mixing device, and using mechanical stirring or high-speed dispersion means to promote uniform mixing of the components to form a mixed material; S4, placing the mixed material into a high-speed dispersing device, setting the dispersing speed to 1000-3000 r / min, and continuing the dispersing time for 30-60 min to ensure that each component in the material reaches a more refined and stable dispersion state; S5. Use a sand mill to grind the high-speed dispersed material until the material is ground into slurry, and the fineness of the slurry is precisely controlled to be less than 50μm to ensure the fineness of the coating particles; S6. Add appropriate pigments to the slurry obtained by grinding, accurately mix the target color, and at the same time, add appropriate amount of thickener to carefully adjust the slurry viscosity according to the construction standards, and finally obtain the finished far-infrared negative ion inorganic coating.

2. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The inorganic binder in S1 includes, by weight, 20-40 parts of silica sol, 10-30 parts of water glass, and 5-15 parts of phosphate.

3. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, wherein: The far-infrared emitting materials described in S1 include, by weight, 10-20 parts of tourmaline, 8-15 parts of Bian stone, 5-12 parts of medical stone, and 3-10 parts of far-infrared ceramic powder.

4. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The negative ion generating material in S1 includes, by weight, 15-25 parts of tourmaline powder, 10-20 parts of negative ion powder, and 8-16 parts of opal.

5. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The filler in S1 includes, by weight, 20-35 parts of calcium carbonate, 10-20 parts of talc, 5-15 parts of titanium dioxide, and 3-10 parts of wollastonite.

6. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The grinding process described in S2 uses a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material ratio is set at 3-5:1, and the grinding time is 2-4 hours.

7. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The S4 high-speed dispersing equipment is equipped with a cooling jacket, which can adjust the material temperature in real time to maintain it at 25-40°C during the dispersing process to prevent the material from heating up due to high-speed friction, resulting in component denaturation or performance degradation.

8. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The internal grinding media of the S5 medium sand mill is made of silicon carbide beads, with a bead size range of 0.8-1.5mm and a filling rate of 70%-85%.

9. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: The pigments used for color matching in S6 are inorganic pigments, including iron oxide and titanium chromium pigments, which are precisely blended according to international standard color cards, and the pigment fineness does not exceed 30μm to ensure uniform and stable colors; the thickeners are hydroxyethyl cellulose and polyurethane associative thickeners, which are accurately measured and added according to the viscosity target of the finished coating, and the viscosity control range is 80-120KU.

10. The method for preparing a far-infrared negative ion inorganic coating according to claim 1, characterized in that: It also includes a finished product testing step, using a spectrometer to test the far-infrared emissivity, which must be no less than 0.85; and using an ion detector to measure the amount of negative ions released to ensure that the amount released is no less than 1,000 per cubic centimeter.